Association between a rule change to reduce home plate collisions and mild traumatic brain injury and other injuries in professional baseball players - Green, G.; D`Angelo, J.; Coyles, J.; Penny, I.; Golfinos, J. G.; Valadka, A. (The American Journal of Sports Medicine, 2019)
Background: Improved player safety is an important goal of professional baseball. Prevention of mild traumatic brain injury (concussion) is an area of emphasis because of the potential for long-term as well as short-term sequelae. Hypothesis: A rule change can lower the incidence of concussions and other injuries in professional baseball. Study Design: Cohort study; Level of evidence, 3. Methods: This study included a retrospective review of data entered concurrently into professional baseball`s electronic medical record system. All minor and major league teams are required to use this system. All injuries are captured by creation of a new record in the system at the time of the injury. All active minor and major league players from 2011 to 2017 were included. The 30 major league clubs have 1200 roster players and play 162 games per season. The approximately 200 minor league clubs have about 7500 active players and play 56 to 144 games annually that combine for approximately 330,000 athlete-exposures per season. Before the 2014 season, Major League Baseball, in conjunction with its players association, instituted a rule limiting home plate collisions between base runners and catchers that applied to both Major League Baseball and Minor League Baseball. All concussions and other injuries at home plate from 2011 to 2017 were analyzed by mechanism and player position. Results: From 2011 to 2013, an annual mean of 100 injuries occurred from home plate collisions in the minor and major leagues, resulting in a mean loss of 2148 days annually. After the rule change, there was a mean 55 home plate collision injuries with 936 days lost per season (P < .0001 for injuries and days lost). A mean 11 concussions attributed to these collisions occurred annually in the minor and major leagues before the rule change, as compared with 2.3 per year after (P = .0029). There were no major league concussions from these collisions after the rule change. The mean annual number of days missed because of concussions at home plate dropped from 276 before 2014 to 36 per year after 2014 (P = .0001). Conclusion: This rule change was associated with significant reductions in the numbers of concussions and other injuries caused by collisions at home plate as well as significant decreases in time lost from play.